The Restless and Relentless Mind of Wes Jackson: Searching for Sustainability - Keller, Harold W. (Journal of the Botanical Research Institute of Texas, 2021)
Robert Jensen. 2021. The Restless and Relentless Mind of Wes Jackson: Searching for Sustainability. (ISBN-13: 978-0-7006-3055-4, hbk). University Press of Kansas, 2502 Westbrooke Circle, Lawrence, Kansas 66045-4444, U.S.A. (Orders: kansaspress.ku.edu/978-0-7006-3055-4.html). $26.95 US, 152 pp., 6" × 9".